Handbook of philosophical logic volume 16 - Gabbay, Dov M.; Guenthner, Franz; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This book is indispensable to any advanced student or researcher using logic in these areas. The chapters are comprehensive and written by major figures in the field. Topics include, Belief Revision, Refutation Systems in Propositional Logic, Quantifier Scope in Formal Linguistics and Non-deterministic Semantics for Logical Systems.
Editorial Preface: Dov M. Gabbay.- Belief Revision: Odinaldo Rodrigues, Dov Gabbay and Alessandra Russo.- Refutation Systems in Propositional Logic: Tomasz Skura.- Quantifier Scope in Formal Linguistics: E. G. Ruys and Yoad Winter.- Non-deterministic Semantics for Logical Systems: Arnon Avron and Anna Zamansky.- Index.
Electronic reproduction.
Keywords: Logic; Electronic books